Participatory Action Research in Software Development: Indigenous Knowledge Management Systems Case Study - Siang-Ting, Siew; Wee, Alvin Yeo; Tariq, Zaman (Springer Berlin Heidelberg, 2013)
Participatory action Research In Software Methodology Augmentation (PRISMA) is a software development methodology which has been amalgamated with Participatory Action Research (PAR). This paper justifies the inclusion of PAR in software development, and describes the PRISMA methodology vis-à-vis a case study. Specifically, the case study encompasses the development of eToro, an Indigenous Knowledge Management System for the Penans, a remote and rural community in Malaysian Borneo.